Characterization of the expression of cytokeratins 5, 8, and 14 in mouse thymic epithelial cells during thymus regeneration following acute thymic involution - Lee, Eun Na (Korean Association of Anatomists, 2011)
The thymus is a central lymphoid organ for T cell development. Thymic epithelial cells (TECs) constitute a major component of the thymic stroma, which provides a specialized microenvironment for survival, proliferation, and differentiation of immature T cells. In this study, subsets of TECs were examined immunohistochemically to investigate their cytokeratin (CK) expression patterns during thymus regeneration following thymic involution induced by cyclophosphamide treatment. The results demonstrated that both normal and regenerating mouse thymuses showed a similar CK expression pattern. The major medullary TECs (mTEC) subset, which is stellate in appearance, exhibited CK5 and CK14 staining, and the minor mTEC subset, which is globular in appearance, exhibited CK8 staining, whereas the vast majority of cortical TECs (cTECs) expressed CK8 during thymus regeneration. Remarkably, the levels of CK5 and CK14 expression were enhanced in mTECs, and CK8 expression was upregulated in cTECs during mouse thymus regeneration after cyclophosphamide-induced acute thymic involution. Of special interest, a relatively high number of CK5(+)CK8(+) TEC progenitors occurred in the thymic cortex during thymus regeneration. Taken together, these findings shed more light on the role of CK5, CK8, and CK14 in the physiology of TECs during mouse thymus regeneration, and on the characterization of TEC progenitors for restoration of the epithelial network and for concomitant regeneration of the adult thymus.